Perlindungan Hukum Terhadap Buruh Perempuan Pada Malam Hari - mukmin zakie (Jurnal Hukum IUS QUIA IUSTUM, 2006)
Both Act No. 13 on the year of 2003 and the Ministery Degree No. 244 on the Year 2003 have already regulated the protection of female workers in the night. Act No. 13 on the Year 2003 emphasizes sanction ifthere Is infrigements.